PAPA and FMF in two siblings: possible amplification of clinical presentation? A case report - Maria Cristina Maggio; Isabella Ceccherini; Alice Grossi; Marco Gattorno; Giovanni Corsello (BMC, 2019)
Abstract Background Familial Mediterranean Fever is a monogenic autoinflammatory disease, typically characterized by recurrent attacks of fever, serositis, aphthous of oral mucosa, erythema. "Pyogenic arthritis, pyoderma gangrenosum and acne syndrome" is a rare autoinflammatory disease with variable expression and typically involving joints and skin. Both the diseases are linked by the overproduction of IL-1. Case presentation We report on the case of two siblings affected by recurrent attacks of fever, oral aphthous stomatitis, abdominal pain, arthritis, undefined dermatitis at the hands, associated with increased AST, ALT, C-reactive protein, erythrocyte sedimentation rate, serum amyloid A, leucocytosis with neutrophilia. Infectious diseases were excluded. The genetic study for Familial Mediterranean Fever, tumor necrosis factor receptor-associated periodic syndrome, Mevalonate kinase deficiency, showed the homozygous mutation p.M680I of exon 10 in MEFV. Their parents were heterozygous for the same mutation p.M680I, however, the mother showed severe symptoms of FMF (recurrent attacks of fever, arthralgia and arthritis, abdominal pain, thoracic pain), the father showed recurrent pustulosis prevalent on the hands and limbs, with arthralgia and abdominal pain. Both the patients started colchicine, with an improvement in clinical manifestations and a reduction of serum amyloid A. For the atypical dermatologic signs present in the two siblings and in the father, the study of other autoinflammatory syndromes was performed with next generation sequencing and showed the heterozygous rare missense mutation of unknown significance: p.(Val408Ile) of PSTPIP1 gene in the two siblings and in the mother, the father was negative. Canakinumab treatment was started in the younger patient, with the resolution of the clinical symptoms and the normalization of serum amyloid A. Conclusions Further studies are needed to better describe the correlation between genotype and phenotype in patients with PAPA syndrome and with PAPA syndrome associated with FMF, considering that the presence of mutations in both genes may amplify clinical presentation and evolution of both diseases.